Genotypes of amyotrophic lateral sclerosis in Mongolia - Daria, Tselmen; Müller, Kathrin; Oidovdorj, Gansuvd; Baatar, Khandsuren; Boldbaatar, Punsaldulam; Sarangerel, Jambal; Rentsenbat, Munkhbayar; Turbat, Sarantsetseg; Yadamsuren, Erdenechimeg; Weydt, Patrick; Dambasuren, Bolormaa; Bosookhuu, Oyungerel; et al. (Journal of neurology, neurosurgery, and psychiatry, 2019)
Amyotrophic lateral sclerosis (ALS) is a multisystem neurodegenerative disease characterised by adult-onset degeneration of the upper and lower motor neuronal systems. The contribution of specific ALS disease genes differs between ethnic groups, at least partially due to founder effects. C9orf72 hexanucleotide repeat expansions (HRE) are the most frequent monogenic cause of ALS in the Western world, but extremely rare in Asian ALS populations, for example in China.1 This fact, together with a predominant C9orf72 risk haplotype in Europe, has fostered the hypothesis that one or very few founder events are responsible for the C9orf72 -linked ALS of European origin.2 However, more profound knowledge about the differences between ALS genetics in European and Asian populations is warranted. We thus set out to characterise ALS genetics in the genetically distinct and relatively homogeneous Mongolian population. - - Patients were recruited from the Department of Neurology, Institute of Medical Sciences of Mongolia, Ulaanbaatar, and neurologists throughout all provinces of Mongolia, from January 2015 to September 2018. All patients met the revised El Escorial criteria for ALS. Due to the lack of a validated neuropsychological test in Mongolian language, fronto-temporal dementia (FTD) diagnosis was established based on clinical impression by an experienced neurologist from the ALS/FTD centre in Ulm, Germany, who was always accompanied by an English-speaking Mongolian physician for translation. Analysis of the HRE in C9orf72 was performed by fragment analysis and repeat-primed PCR, confirmed by Southern blotting. For the SOD1 and FUS mutation screen, Sanger sequencing was employed (primer sequences available on request). For haplotype analysis of C9orf72- HRE positive cases and respective family members, the most conserved risk haplotypes consisting of 15 single nucleotide polymorphisms …
Gesehen am 17.06.2021